Peace education : the concept, principles, and practices around the world - Salomon, Gavriel; Nevo, Baruch (Lawrence Erlbaum Associates, 2002)
This work is intended for scholars and students interested in issues of peace education, reconciliation, and coexistence from several disciplines including social and political psychology, communication, education, political science, sociology, and philosophy.